Mice squeak, we speak :a poem - De Paola, Tomie; Shapiro, Arnold, 1934- (New York : Scholastic, 1997)
Illustrations and simple text describe the ways various animals communicate, such as "Owls hoot," "Pigs squeal," and "Bees buzz."
Elem. School Library Collection
School Library Journal
Publisher's Weekly
1.1
K-3
Keywords: Animal sounds -- Fiction; Animals -- Fiction; Stories in rhyme; Animal sounds -- Fiction; Animals -- Fiction; Stories in rhyme